2013
DOI: 10.1163/15685373-12342094
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgments in Russian Culture: Universality and Cultural Specificity

Abstract: Individuals often deliver rapid, automatic judgments of right and wrong, suggesting that there is an implicit system of knowledge that may guide our moral judgments. Some authors have argued that the principles guiding this system are universal, part of our human endowment. Tests of this hypothesis require rich cross-cultural evidence which is presently limited. Here we extend the current cross-cultural evidence by testing Russian subjects. We focus on three psychological distinctions concerning the nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…As a perspective for future studies, we also propose that dynamics of prosocial decisions may be characterized with intercultural differences. Given that even simple verbal discrimination task performance (Sozinov et al, 2015), as well as social (and moral) decisions in grown-ups (Arutyunova et al, 2013;Simpson and Willer, 2008) differ between cultures, the prosocial behavior may develop in culture-specific ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a perspective for future studies, we also propose that dynamics of prosocial decisions may be characterized with intercultural differences. Given that even simple verbal discrimination task performance (Sozinov et al, 2015), as well as social (and moral) decisions in grown-ups (Arutyunova et al, 2013;Simpson and Willer, 2008) differ between cultures, the prosocial behavior may develop in culture-specific ways.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, a new behavior is subserved by co-activation of systems that had emerged during episodes of learning at successive stages of ontogenesis (Quintana, 1998;Arutyunova et al, 2013). A system elaborated during learning is a set of brain and body elements activity of which provides resultative interaction with the environment (Anokhin, 1974).…”
Section: The Prerequisites Of Prosocial Behavior In Human Ontogenymentioning
confidence: 99%
“…Previous work, using a well-controlled battery of moral dilemmas and a web-based methodology, revealed that subjects’ moral judgments of harm are mediated by the three moral principles, irrespective of whether they are from a heterogeneous Western population (e.g., USA, UK, Canada, Australia, Dutch, urban-educated Mayan; Cushman et al, 2006; Hauser et al, 2009; Abarbanell and Hauser, 2010) or Russian population (Arutyunova et al, 2013). Similarly, Barrett et al’ (2016) study of small scale societies shows that intentionality plays a significant role in most moral judgments, but with some variation in the magnitude of its impact.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work on moral judgments also showed that Russian individuals overall make less extreme judgments than their Western English-speaking counterparts (Arutyunova et al, 2013). Differences in response style do not alter cross-cultural comparisons of averaged responses (Chen et al, 1995).…”
mentioning
confidence: 82%
See 1 more Smart Citation